The Gwithian landscape : molluscs and archaeology on Cornish sand dunes - Walker, Thomas M., (Archaeopress Publishing Ltd, 2018)
Gwithian, on the north coast of Cornwall, is a multiperiod archaeological site. The present work explores the palaeoenvironment of the area around the settlement sites, from the Neolithic, when sand dunes initially developed in the Red River valley, to the present post-industrial landscape.